Subseasonal forecasts of heat waves in West African cities - C. G. Ngoungue Langue; C. G. Ngoungue Langue; C. Lavaysse; C. Lavaysse; C. Flamant (Natural Hazards and Earth System Sciences)
Heat waves are one of the most dangerous climatic hazards for human and ecosystem health worldwide. Accurate forecasts of these events are useful for policy makers and climate services to anticipate the consequences of extreme heat. In particular, subseasonal forecasts are of great importance in order to implement actions to mitigate the consequences of extreme heat on human and ecosystem health. In this perspective, the present study addresses the predictability of heat waves at subseasonal timescales in West African cities over the period 2001–2020. The cities were grouped in three climatic regions based on their climate variability: the continental, Atlantic and Guinean regions. Two types of heat waves were analysed: dry heat waves using 2 m temperature and wet heat waves using average wet bulb temperature. Two models that are part of the subseasonal-to-seasonal forecasting project, namely the European Centre for Medium-Range Weather Forecasts (ECMWF) and the United Kingdom Meteorological Office models, were evaluated using two state-of-the-art reanalysis products, namely the fifth generation ECMWF reanalysis (ERA5) and the Modern-Era Retrospective analysis for Research and Application, Version 2 (MERRA-2). The performance of the forecast models in predicting heat waves is assessed through the computation of categorical metrics such as the hit rate, the Gilbert skill score and the false alarm ratio. The results suggest that at subseasonal timescales, the forecast models provide a better forecast than climatology, but the hit rate and false alarm rate are sub-optimal and the forecasts may be overestimating the duration of heat waves while under-predicting the intensity. Nevertheless, the use of subseasonal forecasts in West African cities can be recommended for prediction of heat wave onset up to 2 weeks in advance.